Development of Test Instruments Using Computer Based Test (CBT) Beesmart in the Evaluation of Aqidah Akhlak Learning at Islamic Senior High Schools in Topoyo, Central Mamuju Regency - Ma’sum; Hamdanah; Marhani; Muhdin; Buhaerah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research aims to develop a computer-based test instrument, the Beesmart Computer-Based Test (CBT) in evaluating Aqidah Akhlak learning at Madrasah Aliyah DDI Topoyo, Central Mamuju Regency. The research method uses the Research and Development development method with the ADDIE model including: 1) Analysis stage, (2) Design stage, (3) Development stage, (4) Implementation stage, (5) Evaluation stage. The results of this research show that: 1) the test instrument developed meets the criteria of being valid, reliable and practical to use. 2) The level of validity of data analysis from material experts is 85.55%, media experts are 90%, each with the category